Efficacy of oral viscous budesonide to reduce dilation treatment after esophageal atresia repair: a retrospective study - Ruggiero, Cosimo; Russo, Giusy; Cozzi, Denis; Ceccanti, Silvia; Scanziani, Chiara; Volpe, Danila; Papoff, Paola; Spatuzzo, Mattia; Spyropoulou, Vasiliki; Oliva, Salvatore (Frontiers in Gastroenterology, 2024)
IntroductionAnastomotic stricture is a common complication following esophageal atresia (EA) repair, substantially affecting the patient’s quality of life (QoL). Multiple dilations are often required to maintain the appropriate diameter of the esophagus, leading to ongoing challenges. The aim of this study is to assess the efficacy of oral viscous budesonide (OVB) in prolonging the time between symptom recurrence and subsequent dilation.MethodsWe carried out a retrospective single-center study for pediatric patients (0–18 years) who had undergone recurrent esophageal dilations (≥3) following EA repair and initiated treatment with OVB (1 mg/day <10 years, otherwise 2 mg/day). Efficacy of treatment was determined by assessing a dysphagia symptom score (DSS) ≤1 for at least 3 months. Recurrence time to dysphagia and dilation were analyzed according to Kaplan-Meier method.ResultsOf 29 patients screened, 19 were enrolled: 19/19 were responsive to OVB and 13/19 (68%) didn’t required further dilations. The median time between dilations was significantly prolonged compared to the pre-treatment period [30 months vs 2 months; p<0.01] as well as the time to dysphagia relapse [18 months vs 1 month; p<0.01].ConclusionTopical budesonide has proven to be an effective treatment for recurrent esophageal stricture in repaired EA. Further investigation is required to assess the long-term sustained response of symptoms to topical steroids.